Mangga Kepal / Muhammad Daniel Rahmat - Rahmat, Muhammad Daniel (2021)
The purpose of this study is to evaluate and observe the reputation of companies towards the marketing approach by which they want to increase consumer awareness of the goods they sell. One of the best methods to attract customers is through social media, such as Facebook. In addition, the study shows how companies promote and advertise their products on social media and Facebook in particular. Facebook has become the best choice because these Facebook users are made up of various ages, no matter young or old. Various techniques are required to publish commodities in each enterprise. Teasers, hard sales, and even soft sales are used in Facebook posts. This is because social media is an effective way to communicate with customers. The more a business reaches an audience, the more likely the conversion company is to have a two -way conversation. Facebook offers various types of ads, it can help businesses access their target clients more easily than others. This will help the company achieve its revenue target. Products sold to their customers also get their interest and attention. Facebook links allow companies and customers to attract and retain customers.